OPTIMIZATION OF SCENARIO SYSTEM MUNICIPAL SOLID WASTE TRANSPORT THAT ARE INTEGRATED WITH THE REGIONAL FINAL DISPOSAL (A CASE STUDY OF THE CITY OF MANADO - TAKAENDENGAN ( NIM : 35312005 ), TEDDY
The rising population size and level of consumption of the population in Indonesia has caused an increase in the solid waste generation volume. Given this condition, good waste management is, therefore, required. The common problems faced by regencies/cities in waste management are the limitation of land for temporary waste disposal site and final waste processing site as well as waste collection and transportation system. The applicable legislation in Indonesia requires that waste management is conducted in the form of collective institution, resources operation and collective/regional final processing site. The objective of this research is to identify the existing condition of waste system, especially in the transportation system, equation model, evaluation and development of waste transportation system scenario on a city and regional scales and optimization of waste transportation system based on the developed models on a city and regional scales. The methods used were direct observation and literature review as well as sampling for obtaining primary and secondary data to develop scenarios based on the transportation path and placement of TPS (temporary waste disposal site) and TPS3R (waste processing site-3R). Some mathematical equations were created with objective function of minimizing the travel time. They were created to calculate the travel time, travel distance, number of trips, number of vehicles, environmental cost and operating cost. The projection of quantity, volume and weight of waste for every regency/city involved in the regional TPA (final processing site) was also calculated. Based on the results of the projection simulation conducted, it was found out that the size of population of Manado city by 2027 was estimated to be 457,672 people and the weight of waste was estimated to be 386.25 tons/day. The scenario were developed into three, namely: scenario I which used direct individual service pattern using collection points; scenario II which used a combination of direct individual service pattern and indirect individual service pattern using collection points and TPS, and; scenario III which used indirect individual service pattern using TPS and TPS3R. The calculation for scenario I yielded number of trips of 190, travel time of 617.89 hours and environmental cost of Rp. 2,150,830 per year for 78 vehicles for collecting and transporting waste. The analysis and evaluation for scenario II yielded number of trips of 163, travel time of 518.24 hours and travel distance of 2,684 km per day. The number of vehicles for transporting waste was 60, the operating cost was Rp. 5,934,000,000, and the environmental cost was Rp. 2,046,743 per year. The calculation for scenario III yielded number of trips of 125, travel time of 334 hours, travel distance of 1,872.7 km per day, operating cost of Rp. 4,423,500,00 for 45 vehicles for transporting waste and environmental cost of Rp 1,434,638 per year. For the regional-scale scenario, by minimizing the travel time, the travel time and number of trips for scenario B were smaller than those of scenario A. Scenario A showed smaller results compared to scenario B for the travel distance, number of vehicles, environmental cost and operating cost. Scenario A, which involved visiting TPST (Integrated Waste Processing Site), showed more optimum results for the operating cost.